Try to prove me wrong: Dialogicity and audience involvement in economics blogs. (August 2018) - Bondi, Marina
Highlights: Blog posts are characterized by forms of self-mention and reader's engagement. The prominence of organizational units responds to a need for greater explicitness. Evaluation and hedges suggest a need to negotiate meanings with an undefined audience. Eliciting response is just as important as promoting the writer's position and ideas. Comments create complex polylogues interweaving parallel conversations and discourses.